Antecedents of Saving Decision at Sharia Banks: Islamic Financial Literacy, Religiosity and Service Quality (Studies on Millennial Generation) - Dhepril Puradi Rachmatulloh; Nihayatu Aslamatis Solekah (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
This article describes the antecedents of saving decisions in Islamic banks which are influenced by knowledge of Islamic finance, understanding of religiosity and service quality. The purpose of this study is to determine the behavior of the Indonesian millennial generation with Islamic financial literacy variables, religiosity and service quality towards the decision to save in Islamic banks. This research is quantitative research by using online questionnaires to respondents who are qualified as millennial generation or their birth years are from 1980 to 1999. The sample used is 170 respondents from the Indonesian millennial generation. The analysis in this research used multiple linear regressions. The results of this study indicated that the Islamic financial literacy variable and service quality had a significant effect on saving decisions. Meanwhile, the religiosity variable did not significantly influence the decision to save. It showed that the millennial generations’ decision to save at Islamic banks has shown their rationality in behavior in the way of increasing financial literacy and choosing good service quality. Meanwhile, their high level of religiosity did not necessarily affect their decision to save at the Islamic Bank.